Uji Kandungan Alkaloid pada Bubuk Kayu Manis ( Cinnamomum burmannii) dengan Metode Sokletasi - Chaterine Juliana Sitorus; Greace Astrid Rotua Hutabarat (International Forum of Researchers and Lecturers, 2024)
The study aimed to investigate the alkaloid content in cinnamon (Cinnamomum burmannii) powder using the Soxhlet extraction method. Alkaloids are organic chemical compounds widely found in nature as secondary metabolites in both plants and animals. They possess a cyclic structure containing one or more basic nitrogen atoms, conferring unique basic properties. The research was conducted to provide a deeper understanding of the potential utilization of plant-derived alkaloids, particularly from cinnamon, in drug development. The study sought to determine the color of the precipitate formed in the extraction solution after the addition of Mayer's reagent and to investigate the effect of the number of Soxhlet extraction cycles on the color of the ethanol used in the research with cinnamon samples. The findings from this study contribute to the exploration of the alkaloid content in cinnamon and its potential applications in pharmaceutical development.